Pengajaran Kosakata Dasar Bahasa Inggris (English Basic Vocabulary) dengan Metode Drilling Untuk Anak-Anak Desa Kalangan Mulur Sukoharjo - Tira Nur Fitria (Universitas Negeri Gorontalo, 2022)
The purpose of this community service activity is to teach and introduce English vocabulary through the drilling method so that it can improve the ability to memorize English vocabulary. The method of community service used is a demo. In carrying out this activity, teaching English vocabulary is carried out using the drilling or retreat method. There are several stages carried out, namely: scheduling the teaching of foreign language vocabulary, presenting English vocabulary material, introducing and using English vocabulary around, inviting children to interpret or define each new vocabulary taught, repeating English vocabulary material, and conducting tests to assess the level of achievement in learning English vocabulary using the drilling method. So that children can master vocabulary easily, fun learning is needed so that children are interested in memorizing English vocabulary. In its use, children must also be able to manage time well by using various drilling methods so that children do not feel bored quickly, enthusiastically, and enthusiastically learning English. Here, the task of educators is to determine and use appropriate English teaching techniques applied to children.